Representational Momentum in the Expertise Context: Support for the Theory of Event Coding as an Explanation for Action Anticipation - Anderson, Dior N.; Gottwald, Victoria M.; Lawrence, Gavin P. (Frontiers in Psychology, 2019)
Abstract This study aimed to extend the notion of the theory of event coding as an explanation of action anticipation in expert sport performers. This was achieved by investigating the degree with which automatic anticipation depends on the ecological congruency between the perceived action and its distal effect. In a novel approach, the representational momentum paradigm was adopted to address this notion. Expert (N=16) and novice (N=20) rugby players observed a dynamic video of a short pass that was displayed as either towards or away from a receiver. Following an occlusion interval, participants were required to judge whether the video resumed at the same place, further forwards or further backwards than its original stopping place. Experts demonstrated stronger anticipatory tendencies when the action was directed towards the receiver. This relationship was modulated by a leftward directional bias that is discussed in the context of a bias in viewing behaviour that is underpinned by attention. Novice anticipatory tendencies were independent of context. These findings show support for the extension of the theory of event coding.